2002
DOI: 10.1149/1.1446874
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diffusion and Oxygen Surface Transfer of La[sub 1−x]Sr[sub x]CoO[sub 3−δ] Studied with Electrical Conductivity Relaxation

Abstract: The chemical diffusion coefficient and oxygen-transfer coefficients of selected compositions in the series La 1Ϫx Sr x CoO 3Ϫ␦ were studied using the conductivity relaxation technique. Measurements were performed in the temperature range 600-850°C and oxygen partial pressure 10 Ϫ4 to 1 bar. Chemical diffusivity and oxygen surface transfer in the La 1Ϫx Sr x CoO 3Ϫ␦ perovskites appear to be highly correlated. The general trend displayed is that both parameters decrease with decreasing p O 2 below about 10 Ϫ2 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 18 publications
(20 reference statements)
13
107
1
Order By: Relevance
“…Generally, a relatively constant value of D Chem is observed when changing the oxygen partial pressure. The values at high oxygen partial pressures are in good agreement with measurements made by van der Haar et al [12] who investigated La 0.8 Sr 0.2 CoO 3−δ . We have previously observed that there is a strong correlation between D Chem and k Ex when fitting relaxation curves, especially when k Ex becomes small.…”
Section: Electrical Conductivity Relaxationsupporting
confidence: 91%
“…Generally, a relatively constant value of D Chem is observed when changing the oxygen partial pressure. The values at high oxygen partial pressures are in good agreement with measurements made by van der Haar et al [12] who investigated La 0.8 Sr 0.2 CoO 3−δ . We have previously observed that there is a strong correlation between D Chem and k Ex when fitting relaxation curves, especially when k Ex becomes small.…”
Section: Electrical Conductivity Relaxationsupporting
confidence: 91%
“…During ECR measurements, the normalized conductivity was monitored as a function of time after a step-wise change in the ambient p O 2 from 0.21 to 0.105 atm in the range 700-900°C. The transient conductivity was fitted to the appropriate solution of Fick's second law of diffusion [34].…”
Section: Characterisationmentioning
confidence: 99%
“…8. Diffusion coefficient and surface exchange rates of STF-50, LSCF, and LSC[34] in dependence on temperature.…”
mentioning
confidence: 99%
“…It has been shown using conductivity relaxation data that the kinetic constant for the oxygen surface exchange reaction (k EX ) of LSC has a relatively strong P O2 dependence (k EX ∝(P O2 ) −n with n approximately equal to 0.5 [21,22]. In contrast, the oxygen vacancy diffusion is relatively independent on P O2.…”
Section: Electrode Kineticsmentioning
confidence: 99%